INTEGRASI PEREKONOMIAN KABUPATEN DAN KOTA DI SUMATERA BARAT MENUJU INTEGRASI PASAR UNTUK MENGHADAPI MASYARAKAT EKONOMI ASEAN 2015 - Anas Yatim, Dr. Ansofino Bin (Jurnal Ipteks Terapan, 2015)
ABSRACTThe focus of this study is to analyse trade integration amongst regencies and cities in West Sumatra province, trade integration between West Sumatra region and Sumatra Economic Corridor area for establishing market integration in encountering ASEAN Economic Community 2015. This study applied an econometric approach Â along with a regression method which was co-integrated and panel data. The result of showed that firstly, trade integration amongst regencies and cities along with West Sumatra province economy is less integrated. This is shown by the value of regression coefficient which was less than the critical value of 5%. The second , the balance of West Sumatra trading and the region of Sumatra economic corridor is influenced more by income per capita with coefficient value 199,58. This value is significant because t test is 3,697 which is higher than tÎ¬ 0,05 (n-2) = 2,31. Another variable i.e distance remote, infrastructure remote and regional dummy variable has not significan over all level testing. Third, factors which influence trade integration between regencies and cities in West Sumatra province used fixed effect method only income perkapita has Â positive significan, while economic growth and infrastructure have korelation negative and not significan. The findings are in line with before result that trading integration amongst regencies and cities in west Sumatra less integrated.Keyword: Economic Integration and Market IntegrationDOI:http://dx.doi.org/10.22216/JIT.2015.v9i2.30Â